2008
DOI: 10.1007/s10620-008-0585-3
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue: The New Endocrine Organ? A Review Article

Abstract: Fat is either white or brown, the latter being found principally in neonates. White fat, which comprises adipocytes, pre-adipocytes, macrophages, endothelial cells, fibroblasts, and leukocytes, actively participates in hormonal and inflammatory systems. Adipokines include hormones such as leptin, adiponectin, visfatin, apelin, vaspin, hepcidine, chemerin, omentin, and inflammatory cytokines, including tumor necrosis factor alpha (TNF), monocyte chemoattractant protein-1 (MCP-1), and plasminogen activator prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
320
0
36

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(366 citation statements)
references
References 85 publications
8
320
0
36
Order By: Relevance
“…Some adipokines also influence adipose tissue development and inflammatory cell recruitment. Leptin and adiponectin are the most studied members of the adipokine family (Maffei et al 1995, Hu et al 1996, but several new members have been discovered recently (MacDougald & Burant 2007, Wozniak et al 2009, Ouchi et al 2011, and since 2007, chemerin has been included in this family of extracellular mediators (Bozaoglu et al 2007, Goralski et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Some adipokines also influence adipose tissue development and inflammatory cell recruitment. Leptin and adiponectin are the most studied members of the adipokine family (Maffei et al 1995, Hu et al 1996, but several new members have been discovered recently (MacDougald & Burant 2007, Wozniak et al 2009, Ouchi et al 2011, and since 2007, chemerin has been included in this family of extracellular mediators (Bozaoglu et al 2007, Goralski et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Until a few years ago, obesity was considered only a condition in which there is an excess accumulation of fat in adipocytes. Recently, however, some studies have shown that the white fat accounting for more than half of mature adipocytes and the remaining of pre-adipocytes, fibroblasts, endothelial cells and macrophages, is a true endocrine organ that plays an important role in both inflammatory and metabolic mechanisms [80,81]. In fact, adipocytes produce at least 50 adipokines, several substances that release chemotactic proteins, complement proteins (adipsin), proteins involved in blood pressure control, angiogenesis, and molecules involved in the metabolism of glucose and lipids including adiponectin, resistin, visfatin, apelin, vaspin, hepcidin, chemeria, and omentin [81,82].…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Recently, however, some studies have shown that the white fat accounting for more than half of mature adipocytes and the remaining of pre-adipocytes, fibroblasts, endothelial cells and macrophages, is a true endocrine organ that plays an important role in both inflammatory and metabolic mechanisms [80,81]. In fact, adipocytes produce at least 50 adipokines, several substances that release chemotactic proteins, complement proteins (adipsin), proteins involved in blood pressure control, angiogenesis, and molecules involved in the metabolism of glucose and lipids including adiponectin, resistin, visfatin, apelin, vaspin, hepcidin, chemeria, and omentin [81,82]. Adipocytes in obese subjects, unlike subjects with normal weight, release a larger amount of proteins from white fat with pro coagulant activity, such as plasminogen activator inhibitor type 1 (PAI-1), factor VII and the inducible form of nitric oxide synthase (iNOS), which at least partly explains the increased risk of cardiovascular disease in obese subjects.…”
Section: Obesity and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…An excess of fat tissue (obesity) has been shown to be harmful for multiple organs and systems through trobogenic, atherogenic, oncogenic, hemodynamic, and neuro-humoral mechanisms [7][8][9][10][11] . Recently, obesity and related diseases (comorbidities), including diabetes mellitus, hypertension, coronary artery disease, cancer, sleep apnea, and osteoartrosis, have replaced tobacco use as a leading cause of death, where obesity contributes directly to the severity of the comorbities [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%